2004
DOI: 10.1002/gcc.20070
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of chromosome 16 loss of heterozygosity in well‐ versus poorly differentiated ductal breast cancer

Abstract: Loss of heterozygosity (LOH) at the long arm of chromosome 16 is a frequent genetic alteration in breast cancer. It can occur by physical loss of part of or the entire chromosomal arm, resulting in a decrease in copy number or loss followed by mitotic recombination. Comparative genomic hybridization (CGH) demonstrated that well-differentiated breast tumors showed significantly more physical loss of 16q than did poorly differentiated ones and that this difference was already discernable in the preinvasive stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
7
50
0
Order By: Relevance
“…Combined global analysis of LOH and genomic copy number data showed that LOH in PCa correlates positively to copy loss. Our data showed no signs of uniparental disomy in LOH regions, as otherwise recently reported to be a common mechanism in advanced breast cancer (Murthy et al, 2002;Cleton-Jansen et al, 2004), acute myeloid leukaemia , medullablastoma (Langdon et al, 2006) and basal cell carcinomas (Teh et al, 2005). Loss of heterozygosity and concomitant copy loss at chromosomes 8p, 10q, 13q,16q and 21q were found with an equal frequency in both localised and metastatic tumours, and were not associated with tumour stage or grade.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Combined global analysis of LOH and genomic copy number data showed that LOH in PCa correlates positively to copy loss. Our data showed no signs of uniparental disomy in LOH regions, as otherwise recently reported to be a common mechanism in advanced breast cancer (Murthy et al, 2002;Cleton-Jansen et al, 2004), acute myeloid leukaemia , medullablastoma (Langdon et al, 2006) and basal cell carcinomas (Teh et al, 2005). Loss of heterozygosity and concomitant copy loss at chromosomes 8p, 10q, 13q,16q and 21q were found with an equal frequency in both localised and metastatic tumours, and were not associated with tumour stage or grade.…”
Section: Discussionsupporting
confidence: 77%
“…Recently it has been shown that LOH regions in the cancer genome often show two copies, despite the loss of one allele (Cleton-Jansen et al, 2004). We therefore tested the correlation between LOH and signal intensities for all samples showing LOH.…”
Section: Comparison Of Loh and Copy Number Alterations In Tumour Dnamentioning
confidence: 99%
“…For instance, physical loss of 16q, the most frequent genomic change observed in grade I tumours, is exceedingly infrequent in high-grade breast carcinomas [2,12,13,33]. Although loss of 16q is observed in a subset of grade III carcinomas, it has recently been shown to occur by a distinct mechanism (LOH in combination with mitotic recombination) [34].…”
Section: Invasive and In Situ Breast Carcinomasmentioning
confidence: 99%
“…Loss of chromosomal material on the long arm of chromosome 16 was observed frequently in several cancers, including breast, prostate, ovarian and fallopian tubes cancer. 43,44 The function of TOX3 is unknown, but a putative high-mobility group motif suggests that it might act as a transcription factor or is involved in the alteration of the chromatin structure. 45 In conclusion, using a Chinese and a German population-based casecontrol study, SNPs in the Chinese and German population associated with breast cancer were identified.…”
Section: Discussionmentioning
confidence: 99%